Effect of Tensile Strength on Treated Bamboo Fiber with Alkali Treatment Compared to Untreated Bamboo Fiber - ABDULLAH, NORHAMIZI ARIEF; HASHIM, MOHD YUSSNI (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The study systematically explored the effect of alkali concentration and soaking time on the microstructure and tensile properties of single-cellulosic. Alkali concentration (w/v%) , immersion time (minute) and immersion temperature (°C) were used as a parameter in alkali treatment conditions optimization determination. Furthermore, the fiber surface morphology and composite breakage microstructure were also investigated experimentally using scanning electron microscope. The single-cellulosic bamboo fiber was immersed in 6 wt.% a NaOH solutions for soaking times of 12, 24, and 48 h. The alkali concentration and soaking time significantly affected the fiber properties. These aspects fit the new worldwide requirements toward the use of renewable and sustainable resources, which warrant the further development of BFC. The tensile properties of the fiber increased after each alkali treatment. The alkali concentration and soaking time significantly affected the fiber properties. The highest tensile strength herein was 290 MPa for the single-cellulosic fiber that was soaked for 12 h in 6 wt.% NaOH. Comparatively, the tensile strength of the single-cellulosic bamboo fiber that was soaked for 24 h in 6 wt.% NaOH was 170 MPa. The tensile modulus of the single-cellulosic fiber was 30 GPa after soaking in 6 wt.% NaOH for 12 h, indicating that a strong alkali treatment negatively affected the stiffness and suitability for use of the fibers in applications. The topography of the fiber surface became much rougher after the alkali treatments due to the removal of hemicellulose and other surface impurities. The alkali treatments substantially changed the morphology of the fiber surface, suggesting an increase in wettability.